Analysis of expert shortcomings of forensic medical examination of victims - Pletenetska, A. (Journal of Education, Health and Sport, 2023)
Traumatic brain injury (TBI) is one of the most significant problems in both clinical and forensic aspects, and is also one of the leading causes of death and disability. Foreign researchers describe various methods of forensic diagnosis of TBI. In order to improve the quality of forensic medical examinations of TBI in Ukraine, there is a need to study the defects of expert assessment. 100 forensic medical commission examinations on the assessment of TBI in injured persons, conducted at the SI "Main Bureau of Forensic Medical Examination of the Ministry of Health of Ukraine", in cases of changed "Expert Conclusions", were studied. The largest number of changed "Conclusions" during the forensic medical examination of corpses in cases of TBI was due to an incorrectly established injury diagnosis of 16±7.2%. Defects that directly affected the experts' incorrect establishment of the diagnosis, mechanism, age and severity of TBI were: insufficient clinical data in medical documentation materials (92±5.3%), incorrect interpretation of clinical data by experts (48±9.8%), lack of involvement of consultants (43±9.7%), failure to take into account accompanying pathological conditions (23±8.2%). Ignoring concomitant pathology in victims had a statistically significant (p<0.05) influence on determining the severity of TBI (85.7±25.9%).